2007
DOI: 10.1007/s00383-007-2036-1
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing expression patterns of Shh and Foxf1 genes in the foregut and lung buds by optical projection tomography

Abstract: Congenital malformations of the foregut are common in humans. The respiratory and digestive tubes are both derived by division of the foregut primordium. Sonic hedgehog (Shh) and Fork head box F1 (Foxf1) genes encode regulatory molecules that play a pivotal role in gut and lung morphogenesis and are therefore important candidate genes to be examined in models of foregut developmental disruption. Optical projection tomography (OPT) is a new, rapid and non-invasive technique for three-dimensional (3D) imaging of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2025
2025

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Ptc expression was unchanged between treated embryos and controls [Ioannides et al, 2003]. With optical projection tomography (OPT), it was possible to visualise Shh and Foxf1 expression patterns in the foregut in detail [Sato et al 2008]. Hajduk et al [2011b] confirmed the diffuse expression pattern of Shh in the AMM foregut and additionally found an abnormal site of Shh expression in the dorsal foregut which correlated with the vicinity and thickness of notochord branches ( fig.…”
Section: Shh Pathwaymentioning
confidence: 55%
“…Ptc expression was unchanged between treated embryos and controls [Ioannides et al, 2003]. With optical projection tomography (OPT), it was possible to visualise Shh and Foxf1 expression patterns in the foregut in detail [Sato et al 2008]. Hajduk et al [2011b] confirmed the diffuse expression pattern of Shh in the AMM foregut and additionally found an abnormal site of Shh expression in the dorsal foregut which correlated with the vicinity and thickness of notochord branches ( fig.…”
Section: Shh Pathwaymentioning
confidence: 55%
“…of critical developmental genes [39,[47][48][49][50]. On the other hand, local mapping of gene expression relative to morphological change, during craniofacial [31] or lung [26] development for instance, provide insight into the possible roles of gene expression in mediating development.…”
Section: Anatomy and Pattern Visualizationmentioning
confidence: 99%
“…This sets an upper specimen size limit. Mouse embryos, especially early embryos are small enough to become 3D visualised with OPT [73,[78][79][80]. Late mouse embryos and mouse fetus must be parted or dissected prior to staining and scanning (e.g.…”
Section: Optical Projection Tomography (Opt)mentioning
confidence: 99%